Jugulotympanic Paraganglioma, Mimicking Chronic Suppura tive Otitis Media (Anwer Khan Modern Medical College Journal, 2012)
Paraganglioma or glomus tumour are named according to their origin. Jugulotympanic  paragangliomas (JTP) originates in the middle ear. There are several diagnostic pitfalls of this tumour. We now report a rare case of JTP in a 47 years old female. Pre-operative diagnosis of this case was chronic suppurative otitis media, Per-operatively it revealed an irregular     somewhat polypoid mass. On histologic examination the mass composed of nests of round to oval cells surrounded by delicate vascular septae and the diagnosis was JTP. Because JTPs are rare tumour and have variable clinical presentation & different histologic findings they are easy to misdiagnose. However this case report may help to generate awareness and to avoid misinterpretation of JTPs.   DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11693   AKMMC J 2012: 3(2): 37-38